2018
DOI: 10.3390/f9100598
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Soil Organic Carbon Stocks and Clay Content under Different Climatic Conditions in Central China

Abstract: Understanding the association between soil organic carbon (SOC) and texture under different climatic conditions is important for assessing the effects of future climate changes on SOC stocks. In this study, we conducted a climatic gradient experiment covering three climate types (humid, sub-humid, and semi-arid) with a steep rainfall ranging from 345 to 910 mm, and specifically determined SOC dynamics, clay content, and vegetation and soil characteristics. The results showed that, from semi-arid to humid regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 62 publications
5
41
0
Order By: Relevance
“…(1) Conserve existing cultivated land patches, appropriately expand grassland and forest land patches The planning of cultivated landscapes and surrounding spaces in the industrial rural areas of Southern Jiangsu should focus on conservation. Agricultural tourism can be developed and landscapes can be enhanced by developing modern circular agriculture and establishing ecological farmsteads [39,40]. Additionally, the construction of facilities such as rural greenways and parks, grassland, and forest land patches can be expanded or even organically merged, thereby increasing the degree of landscape aggregation of these patches and reducing the dominance of construction land patches.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Conserve existing cultivated land patches, appropriately expand grassland and forest land patches The planning of cultivated landscapes and surrounding spaces in the industrial rural areas of Southern Jiangsu should focus on conservation. Agricultural tourism can be developed and landscapes can be enhanced by developing modern circular agriculture and establishing ecological farmsteads [39,40]. Additionally, the construction of facilities such as rural greenways and parks, grassland, and forest land patches can be expanded or even organically merged, thereby increasing the degree of landscape aggregation of these patches and reducing the dominance of construction land patches.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of previous studies, macroaggregates (>2 mm; Qiu et al, ; Wei, Li, Jia, & Shao, ), mesoaggregates (2–0.25 mm; Devine, Markewitz, Hendrix, & Coleman, ; Li, Wang, Ma, & Li, ), or microaggregates (McCarthy et al, ; Shrestha et al, ) might play a dominant role in soil C sequestration. Other studies (DeGryze et al, ; Zhong et al, ) indicated that successional soils accumulated C preferentially as mineral (silt + clay, <0.053 mm)–associated organic matter. For example, Qiu et al () reported that the increases in OC stocks within macroaggregates accounted for 83% and 100% of the total increase in OC stocks in soils at 0‐ to 10‐ and 10‐ to 20‐cm depths after afforestation of abandoned FL, respectively.…”
Section: Introductionmentioning
confidence: 90%
“…It follows that a large number of suspended clay particles and, as a consequence, low transparency of water (Figure 6a) contributed to the natural purification of the Arys River water from incoming pollutants. Besides, the low level of organic pollution in the Arys basin is connected with the prevalence of clay soil, which is poor by organic matter [58].…”
Section: Discussionmentioning
confidence: 99%
“…The toxic pollution of the middle reaches of the Arys River, along with its tributaries, is due to the anthropogenic use of the territory, including the influence of industrial enterprises and agriculture. As with nitrogen compounds (Figure 6c,d), a decrease in toxic pollution downstream can be attributed to the sorbing properties of clay [57,58]. The lowest section of the Arys River, before it flows into the Syr Darya, was characterized by a deterioration in water quality in terms of the content of nitrogen compounds and the WESI index.…”
Section: Discussionmentioning
confidence: 99%